1991
DOI: 10.1002/j.1460-2075.1991.tb07720.x
|View full text |Cite
|
Sign up to set email alerts
|

Histone-DNA interactions and their modulation by phosphorylation of -Ser-Pro-X-Lys/Arg- motifs.

Abstract: The sea urchin sperm‐specific histones H1 and H2B are multiply phosphorylated in spermatids, dephosphorylated in the final stages of spermatogenesis to give mature sperm, and rephosphorylated upon fertilization. Phosphorylation in spermatids, and probably at fertilization, occurs at repeated ‐Ser‐Pro‐X‐Basic‐motifs in the distinctive N‐terminal basic domains of both histones and at the end of the much longer C‐terminal domain of H1. Here we identify the consequences of multiple phosphorylation through comparis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
56
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(58 citation statements)
references
References 50 publications
2
56
0
Order By: Relevance
“…In our in vitro system consisting of only DNA, core histones, and highly phosphorylated linker histones obtained from mitotic cells, there was a distinct negative effect according to the formation of oligonucleosome aggregates, which was neutralized after removal of the phosphate groups with alkaline phosphatase. Our findings therefore support the idea that phosphorylation at mitosis relieves constraints due to loosening of protein-DNA interaction, thereby permitting mechanisms other than H1 histone phosphorylation to condense the chromatin (21).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…In our in vitro system consisting of only DNA, core histones, and highly phosphorylated linker histones obtained from mitotic cells, there was a distinct negative effect according to the formation of oligonucleosome aggregates, which was neutralized after removal of the phosphate groups with alkaline phosphatase. Our findings therefore support the idea that phosphorylation at mitosis relieves constraints due to loosening of protein-DNA interaction, thereby permitting mechanisms other than H1 histone phosphorylation to condense the chromatin (21).…”
Section: Discussionsupporting
confidence: 84%
“…Previous analysis of the structural role of H1 histones demonstrated that three subfractions of H1 histones differ in their effectiveness in condensing DNA fibers into ordered aggregates (17) and that histone subtype H1t, compared with other subtypes, differs in its ability to condense chromatin (18,19). Furthermore, differences in the binding of H1 variants to DNA or phosphorylated H1 histones to DNA have been shown (20,21).The present work was undertaken to extend these earlier binding studies using an in vitro assay developed by Wolffe and Hayes (22), enabling us to systematically study the binding of all known linker histones to a model chromatin complex. The complex is based on a DNA fragment containing the mouse mammary tumor virus long terminal repeat (MMTV LTR) 1 promotor, the chromatin structure of which has been well characterized (23).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…These sperm histones are first expressed in spermatogonia and subsequently function as normal histones in transcription and replication during meiosis due to the fact that their basic N-terminal extensions are phosphorylated and thus neutralized (52). At the late spermatid stage, these N-terminal sequences become dephosphorylated (52) and subsequently stabilize the highly condensed and transcriptionally inert chromatin of the mature sperm by strong ionic interaction with linker DNA (30,36). In contrast, the CS histones constitute the chromatin of the transcriptionally active oocyte and egg (14,35) and participate as maternally stored proteins in chromatin remodeling of the male pronucleus in the zygote (55).…”
Section: Discussionmentioning
confidence: 99%
“…One of these peptides was derived from DNA binding proteins and contained the repeated SPKR motif, which is a substrate for CDKs. They found that a mitotic event indeed greatly improved expression efficiency with this peptide based pDNA carrier and asssumed that phosphorylation in the early phases of mitosis strongly diminished the carriers affinity towards pDNA and thus resulted in pDNA release at the time it has the best chances to enter the daughter nuclei [188]. An additional advantage is that the pDNA is well protected against nucleases in the cytosol until it has the possibility to be enclosed in the daughter nuclei [8].…”
Section: Cell-division Responsive Nanoparticlesmentioning
confidence: 99%